Drive-in movie memories [videorecording (DVD)] - Kuenne, Kurt; Sanders, Don, 1951-; Sanders, Susan, 1950-; Maltin, Leonard; Garland, Beverly, 1926-2008; Corbin, Barry, 1940-; Sanders, Don, 1951-; Sanders, Don, 1951- (Janson Media, 2006)
Presents the history, development, and decline of drive-in movie theaters. Features interviews and commentaries with actors, producers, critics, and others involved in the drive-in movie industry.